Galang Batang SEZ: Advancing the Blue Economy through Strategic Development - Lamidi Lamidi (Journal of Maritime Policy Science, 2024)
The development of the Galang Batang Special Economic Zone (SEZ) is a strategic effort by Indonesia to boost its Blue Economy, leveraging its coastal resources for sustainable economic growth. This study aims to explore the effectiveness of Galang Batang SEZ in advancing Indonesia's Blue Economy by analyzing the zone's infrastructure development, investment climate, and regulatory framework. The research employs a qualitative approach, examining reports, regulations, and investment data collected from government agencies, SEZ administrators, and key stakeholders. Findings reveal that Galang Batang SEZ has successfully attracted significant foreign direct investment, particularly in the alumina refinery and supporting industries, positioning it as a critical hub for marine-based industries. Additionally, the SEZ's focus on sustainable infrastructure, including environmentally friendly power plants and modern port facilities, aligns with the principles of the Blue Economy. However, challenges remain, such as environmental compliance issues and the need for improved local accessibility. The study concludes that while the Galang Batang SEZ shows promise in contributing to Indonesia’s Blue Economy, it requires ongoing policy support, infrastructure enhancement, and environmental management strategies to fully realize its potential. This research underscores the importance of strategic SEZ development in achieving sustainable coastal economic growth and offers insights for future policy implementations in similar zones.